2020
DOI: 10.1177/0890334420904041
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Disialyllacto-N-Tetraose (DSLNT) Content in Milk From Mothers of Preterm Infants

Abstract: Background Human milk oligosaccharides (HMO) have been recognized for the protective effects they may elicit among high risk infants. One HMO, disialyllacto-N-tetraose (DSLNT), has been shown to reduce the risk for developing necrotizing enterocolitis in preterm infants. Research aims To measure DSLNT content in the human milk from mothers of preterm infants, and (1) assess variability; (2) establish correlations between maternal factors and/or an infant’s risk for developing necrotizing enterocolitis; and (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…The HMO results from the current study build upon previous findings in humans, showing reduced DSLNT in MOM received by infants developing NEC, independent of maternal secretor status (17)(18)(19). This is also supported by rodent studies where total and individual HMOs including 2'FL and DSLNT have shown a protective effect against NEC development (16,36,37).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The HMO results from the current study build upon previous findings in humans, showing reduced DSLNT in MOM received by infants developing NEC, independent of maternal secretor status (17)(18)(19). This is also supported by rodent studies where total and individual HMOs including 2'FL and DSLNT have shown a protective effect against NEC development (16,36,37).…”
Section: Discussionsupporting
confidence: 86%
“…A single MOM sample was analysed for each infant, as close to the onset of disease as possible, with control samples matched by day of life (DOL) (online supplementary figure 1). The median DOL of MOM from NEC cases was 18 (IQR 13-34) and from controls was also [18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The DOL of the milk sample is the DOL received by the infant, and is not necessarily the same day as the mother expressed the milk due to standard practice that often involves milk storage.…”
Section: Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, to the above-listed inclusion criteria, the following data were excluded from the data analysis: Preterm milk data from eight articles [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Data from one article reporting concentration from Celiac positive mothers [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…Following a similar model of investigation, early studies implicated DSLNT as an additional protective HMO in rodent models of NEC [183]. More recent epidemiological work has associated low levels of DSLNT in breastmilk with higher risk of NEC [184,185]. Thus, in the near future, supplementation of breastmilk or formula with HMOs may be a viable strategy for reducing the incidence of NEC among premature and low-birth-weight infants [186].…”
Section: Mitigating Inflammation Associated With Preterm Birthmentioning
confidence: 99%